Overcoming institutional voids: Maisons spéciales and the internationalisation of proto-modern brands. Issue 7 (3rd September 2021) - Alexander, Nicholas; Doherty, Anne Marie
Abstract: This article explores the role of institutional voids in the internationalisation of proto-modern brands in London from the mid-1820s through to the early 1850s. Internationalising firms addressed institutional deficiencies in the market through the establishment of retail operations identified here as international maisons spéciales and by adopting marketing strategies designed to legitimate their proto-modern brands. Together, these organisational and strategic marketing responses enabled firms to overcome institutional voids and shape market norms. These mutually supporting organisational and marketing innovations occurred at a much earlier date than the literature currently suggests.